Assessment of podocyte detachment as a pivotal step in the development of focal segmental glomerulosclerosis - Ikbal Ahmed Abdo Elkholy; Wagdi Elkashef; Fatma El-Husseini Mostafa; Amany Hassan (Journal of the Egyptian National Cancer Institute)
Abstract Background Podocytopenia refers to a decrease in the number of podocytes. When podocytes are injured, they may detach leading to podocytopenia, which represents a critical step in the development of podocytopathy and subsequently deterioration of renal functions. Pathological assessment of podocytopenia plays a crucial role in diagnosing underlying kidney diseases. Aim To assess detached podocytes and evaluate their diagnostic role in the development of focal segmental glomerulosclerosis. Materials and methods This is a retrospective study, conducted on 67 archival renal biopsies with the clinical diagnosis of steroid-resistant or steroid-dependent nephrotic syndrome (SRNS) and diagnosed as focal segmental glomerulosclerosis (FSGS) and podocytopathy with detached podocytes by electron microscopy (EM). Colloidal iron stain and Desmin immunohistochemical stain were performed. Assessment of the mean percent of stained pixels in relation to the surface tuft area of the glomerulus, i.e., mean percent of stained area (PSA) was done using image analysis system (ImageJ 1.52a) software. Results Podocytopathy with detached podocytes was diagnosed in 35 (52.24%) cases, while FSGS was diagnosed in 32 (47.76%) cases. Regarding detached podocytes, 27 (49.3%) cases showed no detached podocytes by light microscopy (LM), while only 4 (6%) showed severe podocyte detachment. There was a statistically significant difference between control cases and both podocytopathy with detached podocytes and FSGS regarding mean PSA (p ≤ 0.001). Conclusion Standardized reporting of detached podocyte cells is becoming mandatory as they have a high positive predictive value for the expected EM picture.